Model Keterkaitan Persepsi Nilai, Citra Merek, Kepuasan dan Loyalitas Pelanggan Rumah Sakit - Harmen, Elsa Luvia; Semiarty, Rima; Lita, Ratni Prima (University of Merdeka Malang, 2020)
To maintain the continuity of a business/service is important to retain existing customers. It is necessary to see what factors affect customer loyalty. So the purpose of this study is to find a model of the relationship between perceived value, brand image, satisfaction and customer loyalty. Data are collected from 140 customers who had been treated more than once at the Oncology Clinic in the Ropanasuri Hospital for Special Surgery in Padang to test the relationship model. The results show: 1) perceived value has a positive effect on brand image, 2) perceived value has a positive effect on customer satisfaction, 3) perceived value has no effect on customer loyalty, and 4) brand images have a positive effect on customer satisfaction, the five patient satisfaction has a positive effect on customer loyaltyhttps://doi.org/10.26905/jmdk.v8i2.5094